Singapore's Financial Market: Challenges and Future Prospects - LEE, David K. C. (Institutional Knowledge at Singapore Management University, 2014)
Singapore has successfully developed into one of the leading international financial centers in a short span of less than half a century. The factors of success can be attributed to time, space, and people. Given the complexity and connectivity of today’s markets, there are many challenges in a fast changing environment marked by huge global capital flows and punctuated by crisis after crisis. This chapter will explain the success of Singapore’s financial market and provide the author’s outlook for the island state’s future prospects in the aftermath of the US debt crisis, the Euro crisis, and likely slowdown in emerging markets. In particular, potential problems due to the voluminous capital flow in a time-compressed manner in the small open economy are highlighted.